Exploring How a Shift in the Physical Environment Shapes Individual and Group Behavior across Two Social Contexts. (10th May 2014) - Keiser, Carl N.; Modlmeier, Andreas P.; Singh, Nishant; Jones, Devin K.; Pruitt, Jonathan N.; Foster, S.
Abstract The presence or absence of social counterparts can be instrumental in shaping both individual and collective behaviors. Furthermore, factors of the social environment may safeguard individuals from environmental stressors. In the study reported here, we tested the effects of moving into a new habitat on the mean, variance, and repeatability of individual behavioral tendencies between two social contexts (isolated vs. in a social group). Using the arid social spider, Stegodyphus dumicola (Araneae: Eresidae), we tested whether individuals' boldness was influenced by either (i) their time spent in a social group or (ii) their latency since having moved into a new habitat. We found that the effect of moving into a new habitat on individuals' boldness depended on whether spiders entered the novel environment in isolation or as part of a social group. Spiders that experienced a habitat shift with a social group showed no change in their average boldness, whereas individuals that shifted environments in isolation showed an increase in their mean boldness. Interestingly, neither of these trends was influenced by the time which had elapsed since the habitat shift, suggesting that shifting habitats has a lasting effect on isolated spiders' behavioral tendencies. Finally, we assessed how time spent in a new environment influenced colonies' collective foraging behavior. Here, we found that the longer social groups remained in a new environment, the faster the group responded to prey. Taken together, our data demonstrate that the effects of shifting physical environments on individuals' boldness may depend on individuals' social context, and that group tenure is associated with subtle shifts in colonies' collective foraging behavior.